TARİH BİLİMİNDE FELSEFİ BİR SORGULAMANIN ÖNEMİ ÜZERİNE - Kubilay Aysevener (Felsefe Dünyası)
In this article, I would like to discuss the importance of philosophical inquiry in the science of history. For this reason, my concern is to make explicit definitions of both philosophy and philosophy of history. At the first glance, it seems that there are two different viewpoints in dealing with history: speculative and critical. The speculative view concentrates on discovering general laws which determine the direction of history. The critical view aims to explore the proper method of history. It tries to compare the method of natural sciences with historical investigations. According to critical view, there is a sharp distinction between a study on nature and a study of history in the sense that history has its own special methodology. If the historians want to be accomplished in their work, they have to understand all of the historical facts with philosophical aspects. The historian has no alternative but to accept their philosophical thinking about human life which a necessary requirement for historical understanding of man.